THE INFLUENCE OF STRATEGIC AGILITY ON COMPETITIVE ADVANTAGE WITH ORGANIZATIONAL AMBIDEXTERITY AS MEDIATION AT MSME'S IN BANDAR LAMPUNG - Nurfitriani, Salsa; Rifan, Dinda Fali; Sanjaya, Vicky F. (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2024)
Changes in economic behavior can be an obstacle for MSMEs, because there are still many MSMEs that are not ready for the changes that are occurring. In fact, the changes that often occur in the economic world can actually be used as a success factor for competitive advantage, if the company is able to take the right steps and strategies in a short time. This research aims to show strategies that can be used to increase the competitive advantage of MSMEs by involving strategic agility and through organizational ambidexterity as mediating variables. The population of this research is MSMEs in the culinary sector in Bandar Lampung City, namely 1,162 MSMEs. The total sample was 298 respondents obtained using the Slovin method. The analysis method uses a structural equation model (SEM) approach with the SmartPLS application. The research results show that strategic agility can have a positive and significant effect on competitive advantage. Strategic agility has a positive and significant effect on organizational ambidexterity. Organizational ambidexterity can have a positive and significant effect on competitive advantage. And organizational ambidexterity is able to mediate the influence of strategic agility on competitive advantage. Apart from that, MSMEs must be run in accordance with Islamic business ethics.